THE INFLUENCE OF SERVICE QUALITY, PERCEIVED EASE OF USE, AND TRUST ON CUSTOMER SATISFACTION IN USING THE BCA MOBILE BANKING APPLICATION - Najwan Tsaqib; Khalisa Azalia, Raissa Diamantha Kalila, Rakha Athallah Syahputra, Tineukeu Ariyanti (CV. Adiba Aisha Amira, 2025)
Along with the rapid development of technology, the banking sector is encouraged to adopt digital services to improve customer accessibility and convenience. Mobile banking applications are one of the important innovations that allow customers to make transactions anytime and anywhere. This study aims to analyze the effect of Service Quality, Perceived Ease of Use, and Trust on customer Customer Satisfaction in using the BCA Mobile Banking application. The data in this study were collected through questionnaires distributed to 100 respondents in Jakarta, who were selected based on the criteria of active users of the BCA Mobile Banking application. The data that has been obtained is analyzed using the SEM-PLS model to evaluate the relationship between variables. The results showed that perceived ease of use and trust have a positive and significant effect on customer satisfaction, while service quality has a negative and insignificant impact on customer satisfaction of BCA mobile banking application users. These findings highlight the importance of security, convenience, and trust in creating a positive experience that can encourage loyalty of mobile banking application users. Banks need to prioritize developing easy-to-use features and maintaining customer trust through a secure and reliable system.